A duração da repetição influencia a concentração de lactato sanguíneo e a percepção subjetiva de esforço em protocolos de treinamento no exercício supino - Rodrigo Cesar Ribeiro Diniz (2008)
The duration of a repetition is a variable that may influence the strength training adaptations (TANIMOTO; ISHII, 2006). However, few studies investigated the acute effects of this variable. Therefore, the aim of this study was to investigate the effect of the duration of repetition (self-selected, 4s and 6s) in the blood lactate concentration and in the ratings of perceived exertion (RPE), during and after a training session and also, to verify the relationship between these variables, considering the different durations of repetitions. Nineteen men participated in this study (25,02 (±3,63) years; 80,08 (±9,79) kg: 178,13 (±6,49) cm) with a mean experience in strength training of 30,16 (±31,1) months. In the first and second training sessions, all the volunteers performed 1RM tests for the smith machine bench press exercise. In the third, fourth and fifth training sessions, volunteers performed the training protocol that consisted of 3 sets of 6 repetitions, an intensity of 60% of 1RM and three minutes of rest interval among sets. In each training session, a duration of repetition of 4s, 6 or selfselected was chosen. To avoid order effects, the protocol to be performed was assigned to each subject in a randomized and balanced design. Blood collection was performed before and one minute after the end of each set and the measurement of lactate concentration was done in an equipment Yellow Springs 1500. After the third repetition of each set, researchers asked volunteers to verbalize the RPE in the active muscles (partial active-muscle RPE). Immediately after the end of each set, volunteers should verbalize the RPE in the active muscles (final active-muscles RPE) and in the overall body (0-RPE). Borg's scale of RPE (1970) was the reference for this procedure. Then, analysis of variance in a split-plot arranged in randomized complete blocks design was used to verify blood lactate concentration responses: Friedman s test was used to analyse RPE responses and Spearman's correlation to measure the relationship among these variables. The results showed that the influence of the duration of repetition in the blood lactate concentration depends on the sets. In the first set, there were no significant difference among experimental protocols (a > 0,05). In the second set, 4s and 6s durations were significantly higher than self-selected duration (a < 0,05) and in the third set all durations of repetitions have been different (a < 0,05). The ratings of perceived exertion showed a higher response in local muscles than in overall body (a < 0,05), did not show a set dependent response and also this variable was not able to detect differences in closer durations of repetitions, being higher in 6s than in self-selected duration of repetitions (a < 0,05). The difference between partial active - muscles RPE to final active - muscles RPE was dependent of the set and of the duration of repetition. Considering these results, caution must be emphasized when using RPE as an indicator of training workload. Considering durations of repetitions of 4s and 6s, low and significant (a < 0,05) correlations coefficients between RPE and blood lactate concentration were found, possibly indicating that these variables were influenced by independent factors.